Sex Differences in Cardiac Pathology of SARS-CoV2 Infected and Trypanosoma cruzi Co-infected Mice - Dhanyalayam, Dhanya; Thangavel, Hariprasad; Lizardo, Kezia; Oswal, Neelam; Dolgov, Enriko; Perlin, David S.; Nagajyothi, Jyothi F. (Frontiers in Cardiovascular Medicine, 2022)
Coronavirus disease-2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2; CoV2) is a deadly contagious infectious disease. For those who survive COVID-19, post-COVID cardiac damage greatly increases the risk of cardiomyopathy and heart failure. Currently, the number of COVID-related cases are increasing in Latin America, where a major COVID comorbidity is Chagas’ heart disease, which is caused by the parasite Trypanosoma cruzi. However, the interplay between indeterminate Chagas disease and COVID-19 is unknown. We investigated the effect of CoV2 infection on heart pathology in T. cruzi infected mice (coinfected with CoV2 during the indeterminate stage of T. cruzi infection). We used transgenic human angiotensin-converting enzyme 2 (huACE2/hACE2) mice infected with CoV2, T. cruzi, or coinfected with both in this study. We found that the viral load in the hearts of coinfected mice is lower compared to the hearts of mice infected with CoV2 alone. We demonstrated that CoV2 infection significantly alters cardiac immune and energy signaling via adiponectin (C-ApN) and AMP-activated protein kinase (AMPK) signaling. Our studies also showed that increased β-adrenergic receptor (b-AR) and peroxisome proliferator-activated receptors (PPARs) play a major role in shifting the energy balance in the hearts of coinfected female mice from glycolysis to mitochondrial β-oxidation. Our findings suggest that cardiac metabolic signaling may differently regulate the pathogenesis of Chagas cardiomyopathy (CCM) in coinfected mice. We conclude that the C-ApN/AMPK and b-AR/PPAR downstream signaling may play major roles in determining the progression, severity, and phenotype of CCM and heart failure in the context of COVID.